1063 Depression Moderates the Association Between Posttraumatic Stress Disorder and Nightmare Severity in Nurses. (27th May 2020) - Shapiro, T; Messman, B; Slavish, D C; Alkire, C; Wardle-Pinkston, S; Dietch, J; Kelly, K; Ruggero, C; Taylor, D
Abstract: Introduction: Nurses report a higher prevalence of posttraumatic stress disorder (PTSD) than the general population, and approximately 18% of nurses report having depression. Nightmares are a common symptom of PTSD, and both nightmares and PTSD are correlated with depression. Nightmares may represent a possible clinical target for improving outcomes in both disorders. This study assessed associations between PTSD and depressive symptoms with nightmare severity, and whether depressive symptoms moderated associations between PTSD and nightmare severity. Methods: Participants were 461 nurses (91% female; 77% white, mean age = 38.39 years) recruited from two hospitals for a parent study. Participants completed the Patient Health Questionnaire (PHQ-9), Post-traumatic Stress Disorder Checklist (PCL-5), and 14 days of sleep diaries to assess daily nightmare frequency and severity (on a scale of 0 = not at all severe to 3 = very severe). Results: 22.1% of participants reported at least one nightmare across the 14 days, with a mean daily nightmare frequency of 1.17 (SD = 2.15) and a mean severity of 0.11 (SD = 0.18). PCL-5 and PHQ-9 scores were significantly correlated with nightmare severity (r = 0.27; r = 0.24, respectively) and each other (r = 0.69). PHQ-9 scores moderated the association between PCL-5 scores and nightmare severity (β = -.01, SE = <0.01, p = 0.015). For individuals 1 SD below the PHQ-9 mean, higher PCL-5 scores were associated with higher nightmare severity. For individuals 1 SD above the PHQ-9 mean, higher PCL-5 scores were associated with higher nightmare severity, but to a lesser degree. Conclusion: Both depressive and PTSD symptoms were associated with more severe nightmares. Surprisingly, the association between PTSD symptoms and nightmare severity was stronger for those with lower depressive symptoms. Results suggest depression, PTSD, and nightmares may represent a partially overlapping symptom cluster. Research should investigate how nightmare treatment may reduce PTSD and depressive symptoms. Support: NIAID R01AI128359-01